2017
DOI: 10.1080/13880209.2016.1265986
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of some secondary metabolite content in the seventeen species of the Boraginaceae family

Abstract: Context: The Boraginaceae family comprises plants that have important therapeutic and cosmetic applications. Their pharmacological effect is related to the presence of naphthaquinones, flavonoids, terpenoids, phenols, or purine derivative – allantoin.Objective: In the present study, comparison of some secondary metabolite content and phytochemical relationship between 17 species of the Boraginaceae family were analyzed.Materials and methods: High performance capillary electrophoresis (HPCE) was used to perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
75
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(88 citation statements)
references
References 15 publications
(22 reference statements)
4
75
0
Order By: Relevance
“…Unigenes annotated as HMGCS1, HMGCR, PMVK, and MVD, the four key enzymes of MVA pathway, and PGT, the key enzyme for shikonin biosynthesis, were highly expressed in the root tissue compared to stem and leaf of L. officinale. Previous studies have shown shikonin accumulation in the root of L. officinale [5] while MVA biosynthesis pathway is known to be highly upregulated and specific to the roots. Expression trend for unigenes assigned to shikonin biosynthetic pathway thus is consistent with previously reported metabolome analysis for different tissues of L. officinale.…”
Section: Assemblermentioning
confidence: 95%
See 3 more Smart Citations
“…Unigenes annotated as HMGCS1, HMGCR, PMVK, and MVD, the four key enzymes of MVA pathway, and PGT, the key enzyme for shikonin biosynthesis, were highly expressed in the root tissue compared to stem and leaf of L. officinale. Previous studies have shown shikonin accumulation in the root of L. officinale [5] while MVA biosynthesis pathway is known to be highly upregulated and specific to the roots. Expression trend for unigenes assigned to shikonin biosynthetic pathway thus is consistent with previously reported metabolome analysis for different tissues of L. officinale.…”
Section: Assemblermentioning
confidence: 95%
“…To gain an insight on the highly active biological processes in leaf, stem, and root of L. officinale, RNA-sequencing reads for each tissue were mapped on the de novo transcriptome assembly and unigene expression was measured in FPKM value. Among highly expressed unigenes (FPKM value > 50), 500 unigenes were common across all tissues, while 186, 333, and 346 unigenes were specific to the Zeatin biosynthesis (5) Monobactam biosynthesis (5) Valine, leucine and isoleucine biosynthesis (8) Various types of N-glycan biosynthesis (13) Biotin metabolism (10) N-Glycan biosynthesis (18) One carbon pool by folate (14) Pantothenate and CoA biosynthesis (17) Flavonoid biosynthesis (13) Other glycan degradation (8) Selenocompound metabolism (11) Geraniol degradation (5) Arginine biosynthesis (21) Riboflavin metabolism (14) Aminoacyl-tRNA biosynthesis (22) Sphingolipid metabolism (16) Fatty acid elongation (10) Biosynthesis of unsaturated fatty acids (11) Terpenoid backbone biosynthesis (27) Fatty acid biosynthesis (14) alpha-Linolenic acid metabolism (11) Citrate cycle (TCA cycle) (18) Alanine, aspartate and glutamate metabolism (29) Phenylalanine, tyrosine and tryptophan biosynthesis (27) Inositol phosphate metabolism (25) Metabolism of xenobiotics by cytochrome P450 (8) Drug metabolism -cytochrome P450 (7)…”
Section: Assemblermentioning
confidence: 99%
See 2 more Smart Citations
“…Several chromatographic methods have been developed for determination of allantoin in biological material, while only some of them refer to its quantification in complex plant material. Thus far, the analysis of allantoin in plant matrix was only performed by HPLC in Zea mays and rice (5)(6)(7) and high-performance capillary electrophoresis (HPCE) in comfrey root (8). Due to their simplicity, relatively low cost and short time of analysis, TLC methods are widely used for the separation of secondary metabolites in plant extracts.…”
mentioning
confidence: 99%